Current practice in prevention of bacterial endocarditis. - Durack, D T (1975)
A survey of Oxfordshire dentists showed that most practise prophlaxis of bacterial endocarditis, but that few follow currently recommended regimens. for example, prophylactic antibiotics are started one or more days before the procedure by 72 per cent of dentists, and two or more days before by 25 per cent. Eight-seven per cent administer antibiotics for a total of four or more days. Penicillin is most often given, but tetracyline remains the commonest second choice. Only 12 per cent use intramuscular drugs as first choice, and procaine penicillin is seldom used. These practices are contrasted with current medical recommendations and discussed with reference to fresh experimental evidence on prevention of bacterial endocarditis.